Coherence and the Resolution of Ellipsis. - Kehler, Andrew (Linguistics & Philosophy, 2000)
Despite the attention that various forms of ellipsis have received in the literature, the conditions under which a representation of an utterance may serve as a suitable referent for interpreting subsequent elliptical forms remain poorly understood. This fundamental question remains as a point of contention, particularly because there are data to support various conflicting approaches that attempt to characterize these conditions within a single module of language processing. We show a previously unnoticed pattern in VP-ellipsis data with respect to the type of coherence relation extant between the antecedent and elided clauses. This pattern is explained by an account of how ellipsis resolution processes interact with the inference processes underlying the establishment of these relations. The analysis also explains a similar yet distinct pattern in gapping constructions which are not accounted for by purely syntactic approaches. Finally, we discuss event reference and compare the resulting account to the dichotomy of types of anaphora posited by HanSag.